A comparative study of the effectiveness of β-glucosidase immobilized on CNT-nanoparticles and Ca-alginate beads - Jameel , Ahmad Tariq; Mahmood, Labiba; Yusof, Faridah (Elsevier, 2014)
Enzymes are extensively used in various industrial, biomedical and biopharmaceutical applications. However, enzymes in their free form are unstable and expensive besides being characteristically susceptible to inhibition by high product concentrations and are highly sensitive to pH and temperature changes. Immobilization technology offers solutions to these challenges besides enhancing operational stability, longevity and ease of separation. β-glucosidase has been widely employed as model enzyme for enzymatic studies. Ca-alginate beads provide a gentle environment for immobilization, but have certain limitations such as low stability, high porosity and limitations in biocompatibility. Carbon nanotubes (CNTs) on the other hand have excellent mechanical, thermal and electrical properties, as well as dimensional and chemical compatibility with biomolecules like DNA and enzymes, suitable for biosensor design. Here, β-glucosidase was immobilized in Ca-alginate gel and multi-walled carbon nanotubes (MWCNT) using standard techniques and their activity was compared with that of free enzyme. The activity was found highest (12.53 U/mL) for the free enzyme and lowest (9.768 U/mL) for the immobilized Ca-alginate. The activity of immobilized MWCNT (12.20 U/mL) was close to the free enzyme activity. The enzyme reaction was found to follow Michaelis-Menten kinetics. The Michaelis constants, Km and Vmax, determined using Langmuir linearized plot are respectively 0.09048 μmol/mL and 0.00989 μmol/mL.min for immobilized Ca-alginate; and 0.0985 μmol/mL and 0.01237 μmol/mL.min for immobilized MWCNT. The corresponding values for the free enzyme are 0.0854 μmol/mL and 0.01263 μmol/mL.min. Thus, MWCNT appears to be a promising support material for enzyme immobilization. Keywords: β-glucosidase, immobilization, Ca-alginate, carbon-nanotube, Michaelis-Menten kinetics